The ghostwriter : a novel [large type] - Clark, Julie, 1971- (Thorndike Press large print thriller., 2025)
The Taylor family shatters in a single night when two teenage siblings are found dead in their own home. The only surviving sibling, Vincent, never shakes the whispers and accusations that he was the one who killed them. Decades later, the legend only grows as his career as a horror writer skyrockets. Ghostwriter Olivia Dumont has spent her entire professional life hiding the fact that she is the only child of Vincent Taylor. Now on the brink of financial ruin, she's offered a job to ghostwrite her father's last book. What she doesn't know, though, is that this project is another one of his lies. Because it's not another horror novel he wants her to write. After fifty years of silence, Vincent Taylor is finally ready to talk about what really happened that night in 1975. --